Do disclosures of selective access improve market information acquisition fairness? Evidence from company visits in China - Yang, Jun; Lu, Jing; Xiang, Cheng (Journal of Corporate Finance, 2020)
Following an exogenous regulation change in China, we examine the impact of company visit disclosures on the fairness of market information acquisition. Before July 2012, company visits to Chinese listed firms were vaguely disclosed in annual reports long after they were conducted. After that, they were disclosed in detail within two trading days of their completion. Market reactions around visits are much stronger and more predictive of firms' future earnings if visits occurred after July 2012 and, thus, were disclosed in a timelier and more detailed manner. The timely disclosure of visit details also improves the forecast accuracy of non-visiting analysts, reduces forecast dispersion among analysts, and weakens the relative information advantages of visiting analysts. Because of this, visits are more concentrated on firms with poorer information environments, larger sizes, and manufacturing firms after July 2012, i.e., firms offering visitors larger potential benefits. In summary, the timely disclosure of visit details improves the fairness of information acquisition and decreases information asymmetry while causing information chilling effects for firms that provide fewer potential benefits to visitors.